Stable connotations of mythopoetics of white color in A. Blok’s works: from «Verses аbout the Beautiful Lady» to «The Twelve» - Arshakyan, Edgar (Bulletin of Yerevan University H: Russian Philology, 2022)
The connection between the symbolism of the final image of Christ and the mythopoetics of the “Verses about the Beautiful Lady” occupies a peripheral position in the extensive literature devoted to A. Blok’s poem “The Twelve”, despite the fact that many mythopoetic features in Blok’s late lyrics were formed in “Verses аbout the Beautiful Lady” or in certain correlation to them. The article observes the genesis of mythopoetic concept of white color in Blok’s early lyrics in the context of connotations relevant to the finale of “The Twelve”, which were formed under the influence of Andrey Bely’s ideas. The formation of the mythopoetic semantics of white color in Blok’s early lyrics was significantly influenced by the mystical interpretation of the color symbolism by A. Bely and the discussion of the subject in the early correspondence of the two poets. However, Bely’s ideas underwent certain refraction in the Blok’s artistic consciousness. The cycle 15 poems by Blok published in 1904 in the almanac “Grif”, his book “Poems about Russia” (1915) as well as the finale of the poem “The Twelve” (1918) have been analyzed from the point of view of mythopoetic concept of white color. Special attention has been paid to the compositional features of the studied pieces. The analysis shows that the actual connotations of white color mythopoetics in these works are associated with the dialectical triad and the idea of ​​synthesis, as well as with the motifs of love and fidelity, referring to the biblical context.